+0

# Nth term

0
149
1

whats the nth term of 2,8,18,32

Guest Feb 22, 2017

#1
+19084
+25

whats the nth term of 2,8,18,32

$$\small{ \begin{array}{lrrrrrrrrrr} & {\color{red}d_0 = 2} && 8 && 18 && 32 && 50 && \cdots \\ \text{1. Difference } && {\color{red}d_1 = 6} && 10 && 14 && 18 && \cdots \\ \text{2. Difference } &&& {\color{red}d_2 = 4} && 4 && 4 && \cdots \\ \end{array} }$$

$$\boxed{~ \begin{array}{rcl} a_n &=& \dbinom{n-1}{0}\cdot {\color{red}d_0 } + \dbinom{n-1}{1}\cdot {\color{red}d_1 } + \dbinom{n-1}{2}\cdot {\color{red}d_2 } \end{array} ~}$$

$$\begin{array}{|rcll|} \hline a_n &=& \dbinom{n-1}{0}\cdot {\color{red} 2 } + \dbinom{n-1}{1}\cdot {\color{red} 6 } + \dbinom{n-1}{2}\cdot {\color{red} 4 } \\\\ && \binom{n-1}{0} = 1 \\ && \binom{n-1}{1} = n-1 \\ && \binom{n-1}{2} = \left( \frac{n-1}{2} \right) \cdot \left( \frac{n-2}{1} \right)\\\\ a_n &=& {\color{red} 2 } + (n-1)\cdot {\color{red} 6 } + \left( \frac{n-1}{2} \right) \cdot (n-2) \cdot {\color{red} 4 } \\ &=& {\color{red} 2 } + (n-1)\cdot {\color{red} 6 } + (n-1) \cdot (n-2) \cdot {\color{red} 2 } \\ &=& 2 + 6n-6 + (2n-2) \cdot (n-2) \\ &=& -4 + 6n + 2n^2-4n-2n+4 \\ \mathbf{a_n} & \mathbf{=} & \mathbf{2n^2} \\ \hline \end{array}$$

Example:

$$\begin{array}{|rclcl|} \hline a_1 &=& 2\cdot 1^2 &=& 2 \\ a_2 &=& 2\cdot 2^2 &=& 8 \\ a_3 &=& 2\cdot 3^2 &=& 18 \\ a_4 &=& 2\cdot 4^2 &=& 32 \\ a_5 &=& 2\cdot 5^2 &=& 50 \\ \dots \\ \mathbf{a_n} &\mathbf{=}& \mathbf{2\cdot n^2} \\ \hline \end{array}$$

heureka  Feb 22, 2017
Sort:

#1
+19084
+25

whats the nth term of 2,8,18,32

$$\small{ \begin{array}{lrrrrrrrrrr} & {\color{red}d_0 = 2} && 8 && 18 && 32 && 50 && \cdots \\ \text{1. Difference } && {\color{red}d_1 = 6} && 10 && 14 && 18 && \cdots \\ \text{2. Difference } &&& {\color{red}d_2 = 4} && 4 && 4 && \cdots \\ \end{array} }$$

$$\boxed{~ \begin{array}{rcl} a_n &=& \dbinom{n-1}{0}\cdot {\color{red}d_0 } + \dbinom{n-1}{1}\cdot {\color{red}d_1 } + \dbinom{n-1}{2}\cdot {\color{red}d_2 } \end{array} ~}$$

$$\begin{array}{|rcll|} \hline a_n &=& \dbinom{n-1}{0}\cdot {\color{red} 2 } + \dbinom{n-1}{1}\cdot {\color{red} 6 } + \dbinom{n-1}{2}\cdot {\color{red} 4 } \\\\ && \binom{n-1}{0} = 1 \\ && \binom{n-1}{1} = n-1 \\ && \binom{n-1}{2} = \left( \frac{n-1}{2} \right) \cdot \left( \frac{n-2}{1} \right)\\\\ a_n &=& {\color{red} 2 } + (n-1)\cdot {\color{red} 6 } + \left( \frac{n-1}{2} \right) \cdot (n-2) \cdot {\color{red} 4 } \\ &=& {\color{red} 2 } + (n-1)\cdot {\color{red} 6 } + (n-1) \cdot (n-2) \cdot {\color{red} 2 } \\ &=& 2 + 6n-6 + (2n-2) \cdot (n-2) \\ &=& -4 + 6n + 2n^2-4n-2n+4 \\ \mathbf{a_n} & \mathbf{=} & \mathbf{2n^2} \\ \hline \end{array}$$

Example:

$$\begin{array}{|rclcl|} \hline a_1 &=& 2\cdot 1^2 &=& 2 \\ a_2 &=& 2\cdot 2^2 &=& 8 \\ a_3 &=& 2\cdot 3^2 &=& 18 \\ a_4 &=& 2\cdot 4^2 &=& 32 \\ a_5 &=& 2\cdot 5^2 &=& 50 \\ \dots \\ \mathbf{a_n} &\mathbf{=}& \mathbf{2\cdot n^2} \\ \hline \end{array}$$

heureka  Feb 22, 2017

### 21 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details